Exploring inconsistencies, trends and forecasting of wheat production in Bangladesh: a statistical analysis approach - Sharmin, Sajia; Meem, Maliha Sultana; Das, Keya Rani (Annals of Bangladesh Agriculture, 2025)
After rice, wheat is the another most imperative source of staple foods in Bangladesh. Wheat production plays a crucial role in ensuring food security. However, persistent inconsistencies between wheat production and cultivated area pose challenges to national food security. This study investigates the trends, variability, and forecasting of wheat production in Bangladesh from 1971 to 2023. Secondary data were collected from the Bangladesh Bureau of Statistics and the Department of Agricultural Extension. The entire period was divided into two periods: 1971–2000 and 2001–2023. A semi-log model was used to estimate the growth rate, while a linear regression model examined the dependency of wheat production on cultivated area. The coefficient of variation (CV) was applied to assess variability, and the Autoregressive Integrated Moving Average (ARIMA) model was employed for forecasting wheat production. A steady decline in the area of wheat cultivation and fluctuations in wheat production was visible throughout the study period. A moderate positive correlation between area and production was observed, which indicates that area under cultivation has an influence on production of wheat in Bangladesh. While the growth rate was unstable throughout the study period with significant variability. The underlying patterns in wheat production was successfully identified by the ARIMA (1,1,0) model providing meaningful forecasts. This paper forecast the wheat production for upcoming 5 years. A consistent trend was detected emphasizing key stages of increase and decrease of wheat production in Bangladesh. To wrap up, though wheat production in Bangladesh has made some improvement, the country deals with a continuous struggle to meet the demand. Strategies to ensure more stable and increased wheat production must be prioritized by the policymakers. Ann. Bangladesh Agric. 29(1): 51-67